PENGARUH KREATIVITAS IKLAN DAN KREDIBILITAS ENDORSER TERHADAP EFEKTIFITAS IKLAN (Studi Kasus Pada Iklan Olay Natural White Di Kota Semarang) - Nurhayati, Eva (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2012)
Olay personal product performance data in 2011 showed that TOM of Olay brand was 3.8 lower than the advertising TOM 11.0, which means that consumer recall of Olay ad is much higher compared to its products itself, it means consumers are more aware of its brand than the product itself. This indicates a problem in the advertising effectiveness of the Olay brand. Based on these findings the research problem formulated is â€œHow to improve the advertising effectiveness through advertising creative and advertising endorser by taking advertising attractiveness factor into account.â€To answer the problem, data about the credibility of the endorser, advertising creativity, effectiveness of advertising, and advertising appeal is required. The data is obtained through interviews with 100 women respondents who lives in the city of Semarang and ever see / know the Olay face whitening ad. The data then is analyzed using Structural Equation Modeling analysis techniques.The test result using the analysis techniques of Structural Equation Modeling indicates that the model is fit to population data. While from hypothesis testing showed that all five hypotheses can be accepted and proven in this study, namely that the effectiveness of advertising is influenced by endorser credibility and advertising creativity and advertising attractiveness is influenced by endorser credibility, advertising creativity, and advertising attractiveness.